Prevalensi Skabies dan Faktor Risiko Pada Pemilik Kucing yang Berkunjung ke RSH Provinsi Sumatera Selatan : Studi Potong Lintang - Winda Wahyu Setya Rahmah; Hamzah Hasyim; Yuanita Windusari (Journal of Pharmaceutical and Sciences, 2026)
Scabies is a skin disease caused by infection with the Sarcoptes scabiei mite, and its incidence has increased worldwide in recent years. In addition to personal hygiene factors associated with scabies prevalence, close contact with infected pets also increases the risk of scabies transmission. This study aims to identify risk factors associated with scabies among cat owners at Visiting South Sumatra Provincial Animal Hospital. This study was a quantitative analysis with a cross-sectional design conducted from August to October 2023 at the Animal House of South Sumatra. A total of 112 respondents were recruited using a simple random sampling technique. The independent variables in this study were the use of antiseptics or soap, cleanliness of clothes, cleanliness of towel, cleanliness of bed sheets, and methods of keeping cats, while the dependent variable was scabies. Data analysis was performed using univariate and bivariate methods using the chi-square test with a significance level of p < 0,05 and a 95% confidence interval (CI). Statistical analysis showed that 21,5% of respondents experienced scabies. Scabies was influenced by the use of antiseptics or soap (p-value = 0,0001), clothing cleanliness (p-value = 0,019), towel cleanliness (p-value = 0,001), and methods of keeping cats (p-value = 0,0001). There was no significant association between bed linen cleanliness (p-value = 0,222) and scabies incidence among cat owners visiting the South Sumatra Animal Husbandry Hospital (RSH). Based on the study results, it was concluded that scabies incidence in cat owners was significantly related to personal hygiene behaviors and pet care management. Therefore, pet owners are advised to improve personal hygiene and good pet care management as a preventative measure against scabies transmission.